Sexual presence and intentional dynamics: deviant and non-deviant sexual self-regulation from the first person stance - Renaud, P. (2012)
Child molesters (n=13) and sexually non-deviant subjects (n=29) were immersed with virtual characters depicting relevant sexual features while their sexual arousal and gaze behaviour were assessed to characterize their sexual preferences and intentional dynamics. Sexual arousal was measured using circumferential penile plethysmography (PPG). Gaze behaviour dynamics was derived from average gaze radial angular deviation (GRAD) and GRAD coefficient of variation (GRADCV). Results show distinct sexual arousal profiles according to sexual preferences and point towards the existence of specific gaze behaviour dynamics guided by sexual intentions. Theoretical interpretations are based on the ecological psychology of J.J. Gibson and the integrated theory of sexual offending (Ward, 2009; Ward & Beech, 2006). Theoretical underpinnings coming from these approaches are advocated as being especially well suited to explain how virtual reality can help probing into child molesters’ phenomenology as lived from the first-person stance.